2017
DOI: 10.1111/pbi.12703
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of bacteriophage lytic proteins against Streptococcus pneumoniae in the chloroplast of Chlamydomonas reinhardtii

Abstract: SummaryThere is a pressing need to develop novel antibacterial agents given the widespread antibiotic resistance among pathogenic bacteria and the low specificity of the drugs available. Endolysins are antibacterial proteins that are produced by bacteriophage‐infected cells to digest the bacterial cell wall for phage progeny release at the end of the lytic cycle. These highly efficient enzymes show a considerable degree of specificity for the target bacterium of the phage. Furthermore, the emergence of resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 65 publications
0
33
0
1
Order By: Relevance
“…The reported yields are generally in the range of 0.1 to 5 % total soluble protein (TSP), although caution should be exercised when making comparisons, since the preparation of soluble extracts and the assay used for quantification differ between groups. A better measure is perhaps protein yield per gramme of dried biomass [31]. Whilst such levels are below those of established recombinant platforms, new synthetic biology approaches (see below) and moleculargenetics strategies based on our understanding of chloroplast gene regulation in C. reinhardtii are now leading to significant improvements in yield.…”
Section: The Algal Chloroplast As a New Bio-factorymentioning
confidence: 99%
See 1 more Smart Citation
“…The reported yields are generally in the range of 0.1 to 5 % total soluble protein (TSP), although caution should be exercised when making comparisons, since the preparation of soluble extracts and the assay used for quantification differ between groups. A better measure is perhaps protein yield per gramme of dried biomass [31]. Whilst such levels are below those of established recombinant platforms, new synthetic biology approaches (see below) and moleculargenetics strategies based on our understanding of chloroplast gene regulation in C. reinhardtii are now leading to significant improvements in yield.…”
Section: The Algal Chloroplast As a New Bio-factorymentioning
confidence: 99%
“…These include hormones such as human growth hormone [28], anti-hypertensive peptides [45], cancer therapeutics [46], antibody mimics [47], autoantigens [48], wound-healing factors [47] and anti-bacterial enzymes [31]. These examples serve to illustrate the potential of the chloroplast as a platform for a wide variety of recombinants.…”
Section: Other Therapeutic Proteinsmentioning
confidence: 99%
“…Having demonstrated that three foreign proteins could be synthesized in a single transgenic line, we then sought to further engineer this line by addition of two more transgenes at a second locus. We therefore built a second transformation plasmid (named pAP) that was designed to target the aadA cassette that confers spectinomycin-resistance [35] and a cassette for expression of the endolysin gene cpl-1 [29] into the middle of the non-essential chloroplast gene, chlL. This gene encodes a subunit of the dark-operative protochlorophyllide reductase and a knockout of chlL gives rise to a 'yellow-in-the-dark' phenotype [36].…”
mentioning
confidence: 99%
“…1. Since the cpl-1 gene was designed to encode an HA-tagged version of Cpl-1 [29], we anticipated that Western analysis of the ICS3-AP transformants using the anti-HA antibodies would demonstrate the synthesis of four different recombinant proteins: namely, Cpl-1, together with IBV-CTB, CodA and SplB. However, only Cpl-1 and IBV-CTB could be detected in the three transformant lines despite CodA and SplB being readily detectable in the ICS3 recipient line (Fig.…”
mentioning
confidence: 99%
“…. É importante notar que a maioria das proteínas foram clonadas no cloroplasto e apenas três delas no núcleo.Tabela 2.2: Resumo das biomoléculas expressas em Chlamydomonas reinhardtii, organela geneticamente transformada, percentual de expressão (%) da proteína solúvel total, concentração em miligramas por litro (mg / L) e vetor de clonagem STOFFELS et al, 2017(RASALA et al, 2012).…”
unclassified